Performance of MIMO and Relay Communication System using TGn and HH Channel. Issue 1 (June 2019) - Hanafi,; Hendrantoro, G.
Abstract: The research on relay communication systems and MIMO has been done by researchers. Both systems have advantages in increasing the system performance and capacity. While the OFDM transmission technique has the advantage to avoid ISI from receiving signals. Systems are simulated to obtain BER as a system performance parameter and determine the increase in BER due to the use of a relay and 2 antennas in communication systems. Systems are compared between relay system with the non-relay system, where both systems are simulated too for using 2 antennas and 1 antenna. Messages are sent using the OFDM technique over TGn and the HH channel. Systems with 2 antennas use the Alamouti scheme. Received messages are combined using MRC, and the original messages are detected using an ML detector at the receiver. The increase in BER obtained between relay systems compared to non-relays is 1.69 and 2.02 times when using 1 and 2 antennas on Eb/No = 9 dB. Increased BER also occurs between 2 antenna systems compared to system 1 antenna, which is 79.71 times in non-relay systems and 94.93 times in relay system on Eb/No = 9 dB. From these results, it can be seen that there is an increase in BER in the use of a relay and 2 antennas in the system. The BER system that occurs, both using the TGn channel and the HH channel, shows relatively the same results.